Paleomagnetism of the Matuyama Reversed basalts from Gembudo, Japan and Reykjavik, Iceland - 堂面, 春雄 (山口大学教育学部, 1991)
The present author has made the paleo/rock magnetic studies on the ”Matuyama Reversed Rocks” come from both Gembudo area, Japan and the north of Reykjavik, Iceland. All of these samples show the reversed natural remanent magnetizations